A Broadband Circularly Polarized Antenna with Stable Gain Based on Square Slotted Ground. (1st March 2023) - Li, Mingshun; Song, Wei; Sheng, Xinqing
Abstract: In this paper, a circularly polarized (CP) low cost, low profile antenna with broadband stable gain is proposed. The antenna consists of a grounded square slot with two inverted-L shaped microstrips, an asymmetrical Y-shaped microstrip radiator with a stub, and several fine tuning elements. The CP radiation is first realized by using the Y-shaped microstrip line, which incorporates a stub is to realize better impedance matching. Next, by utilizing two Inverted-L microstrips into the corners of the grounded slot, the axial ratio (AR) characteristic can be further improved. A wider AR bandwidth (ARBW) can be achieved by utilizing four rectangular strips as fine tuning elements. Simulation results show the proposed antenna demonstrates a radiation with a CP bandwidth of 50% and a stable gain with average value of 5.18 dBi.